2007
DOI: 10.1021/jp074686u
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pt,Sn/Mg(Al)O Catalysts for Light Alkane Dehydrogenation by FT-IR Spectroscopy and Catalytic Measurements

Abstract: The Pt function in Pt,Sn/Mg(Al)O and in Pt/Mg(Al)O catalysts has been studied by a combination of catalytic testing for ethane dehydrogenation at 450−650 °C under a C2H6/H2/CO2/N2/Ar = 10:1.6:6.8:5.9:75.7 flow and Fourier transform infrared spectroscopy (FT-IR), using CO as a probe molecule. The acid−base properties of the support were also investigated by FT-IR, using CH3CN as a probe molecule. CO adsorption experiments revealed the presence of Pt terraces, as well as Pt sites with low coordination number (st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 55 publications
4
77
0
Order By: Relevance
“…This can probably be achieved even with a small amount of Sn introduced on Pt catalysts because Sn atoms are known to decorate step sites. 16 The lack of reactive Pt steps on Pt 3 Sn(211) suppresses propene dehydrogenation, which explains in part the increased selectivity. In addition, the weaker propene adsorption identified here and in earlier studies 8,21 has a positive impact on the selectivity as propene desorption becomes easier.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…This can probably be achieved even with a small amount of Sn introduced on Pt catalysts because Sn atoms are known to decorate step sites. 16 The lack of reactive Pt steps on Pt 3 Sn(211) suppresses propene dehydrogenation, which explains in part the increased selectivity. In addition, the weaker propene adsorption identified here and in earlier studies 8,21 has a positive impact on the selectivity as propene desorption becomes easier.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Industrially, Pt is used for LAD due to its intrinsic nature of favoring C-H bond activation over C-C bond activation [2]. The addition of Sn as a promoter results in higher olefin selectivity and catalyst stability [3][4][5][6][7][8][9][10][11][12]. The promotional effects have been attributed to the formation of Pt-Sn alloys [3,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that metal oxide supports including K-L zeolite, spinels, alkali-doped alumina, calcined hydrotalcite greatly suppressed coke formation due to the free of acid sites and low alkene adsorption [32][33][34][35][36][37]. Among these supports, the studies about the calcined hydrotalcite (Mg(Al)O) or hydrotalcite-like materials were especially attractive due to their moderate basic characteristics and high thermal stability.…”
Section: Introductionmentioning
confidence: 99%